2007
DOI: 10.1097/gco.0b013e32801195c9
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography imaging for gynecologic malignancy

Abstract: The role of PET or PET/computed tomography has evolved from a diagnostic tool into a potential indicator of response to treatment and prognosis. Evaluating this tool by clinical impact is an attractive end point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 47 publications
0
25
0
3
Order By: Relevance
“…According to Esajas et al [50], serial SCC measurements during the follow-up do not improve the cure rate of patients who will ultimately develop a recurrence. However, it has been recently reported that the performance of a PET in patients with asymptomatic SCC elevation can sometimes allow an earlier diagnosis of relapse, with positive effects on patient survival [59,60,62]. PET imaging appears to have the potential to improve both the clinical outcome and the quality of life of patients with recurrent cervical cancer [60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Esajas et al [50], serial SCC measurements during the follow-up do not improve the cure rate of patients who will ultimately develop a recurrence. However, it has been recently reported that the performance of a PET in patients with asymptomatic SCC elevation can sometimes allow an earlier diagnosis of relapse, with positive effects on patient survival [59,60,62]. PET imaging appears to have the potential to improve both the clinical outcome and the quality of life of patients with recurrent cervical cancer [60].…”
Section: Discussionmentioning
confidence: 98%
“…Positron emission tomography with 18-fluorodeoxyglucose [FDG-PET] has been employed in patients treated for squamous cell cervical cancer who had asymptomatically elevated SCC levels but negative or equivocal findings at other imaging modalities [59][60][61][62]. Chang et al [60] performed PET in 27 patients who experienced a complete response to primary or salvage therapy, who presented no evidence of disease by conventional methods and who had serum SCC > 2.0 ng/ml in two consecutive samples.…”
Section: Serum Scc Assay In the Monitoring Of Response To Treatment Amentioning
confidence: 98%
“…18 F-FDG PET has prognostic value in OSCC patients (13,19,20). Notably, 18 F-FDG uptake in the primary tumor predicts overall survival in different cancers (21)(22)(23)(24)(25)(26), including OSCC (27). However, little has been reported about the prognostic significance of PET findings in the neck lymph nodes in patients with OSCC.…”
mentioning
confidence: 99%
“…Numerous studies have shown that rapidly growing neoplastic tissue utilises glucose as a substrate for energy needs, thus producing an increased uptake of 18 F-FDG [15]. Even though the tracer is not tumour-cell specific, 18 F-FDG is widely used in the study of many malignant diseases [16,17], as it is considered better than conventional imaging in identifying primary or secondary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have shown that the reduction in the number of malignant cells fini energetici, determinando un aumento dell'uptake del 18 F-FDG [15]. Sebbene tale tracciante non sia specifico della cellula tumorale, la 18 F-FDG-PET risulta largamente utilizzata nello studio di molte patologie neoplastiche [16,17] Nel nostro studio, le metodiche mostrano una concordanza con valori di sensibilità, specificità ed accuratezza superiori ai dati della letteratura poiché, la maggior parte degli studi finora effettuati utilizzano la TC senza la somministrazione di MdC organo-iodato, che non permette la visualizzazione di molte metastasi epatiche [17][18][19]. Anche se le localizzazioni secondarie epatiche mostrano una evidente ipercaptazione di 18 Sebbene la PET e la TC risultano, dai dati di questo lavoro, equivalenti nella capacità di identificare localizzazioni secondarie epatiche, appare chiaro che le due metodiche sono tra loro complementari.…”
Section: Discussionunclassified